Segmentation of the Sensor Data Stream in Pervasive Smart Environments - Vahid Ghasemi; Mohammad Javadian; Sajad Hayati (مدیریت مهندسی و رایانش نرم)
Nowadays, pervasive environment development has garnered lots of attentions. In such environments, user-object interactions along time are recorded via several sensors, and sensor events are processed as a stream of data. In this process, user’s activities are recognized, and accordingly, essential services are provided. In many activity recognition approaches, firstly the input data stream is segmented, then the activity pertaining to each segment is induced. In such approaches, sensor data stream segmentation is a predominant phase. In this paper, this problem is investigated and a novel method, based on a difference of convex programming problem, is proposed to solve it. In the proposed method a feature vector is calculated for each sensor event in the data stream using a Bayesian approach, and the sequence of such vectors is hired in a difference of convex cost function. The cost function and feature vectors has been calculated by considering heuristics adopting to smart environments. Data segments are extracted by minimizing the cost function. The segmentation purity and conditional entropy have been calculated to measure the performance. Evaluations show that the proposed method has an acceptable performance comparing to some existing approaches.